Theoretical Model of Behavioral Consequences of Faith in Conspiracy Theory - Yarosh, Nina; Artiukhova, Vladyslava (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The article analyzes researches of recent years on the current issues of studying psychological features of faith in conspiracy theory. It is noted that the relevance of this issue is determined by the lack of thorough theoretical and empirical research on the above issue. The authors for the first time reviewed and generalized analysis of socio-psychological predictors of belief in conspiracy theory and its behavioral consequences. It is determined that belief in conspiracy theory is associated with socio-political conditions (stressful situation of uncertainty in society, distrust of power, low social status, political cynicism, low level of education, etc.), individual psychological (schizotypal traits, neuroticism, mistrust, anxiety, insecurity, narcissism) and cognitive factors (conspiratorial type of thinking, etc ..) Analysis of literature revealed a number of positive and negative consequences of faith in the theory of conspiracies, which are sometimes contradictory. The result of this analysis is the proposed theoretical model of behavioral consequences of faith in conspiracy theory. In addition, the authors emphasize the generalization of the study results of conspiracy theories impact related to the spread of the COVID-19 virus on the implementation of preventive measures by the population. It is noted that people with a high conspiracy mentality are more likely to engage in abusive prevention behaviors, but are less likely to adhere to government-initiated preventive behaviors, although the perceived risk of death and motivation to defend themselves can minimize this trend.